2019
DOI: 10.5039/agraria.v14i4a7310
|View full text |Cite
|
Sign up to set email alerts
|

Índices de vegetação na estimativa da produtividade do feijoeiro cultivado sob doses de nitrogênio

Abstract: RESUMO: O sensoriamento remoto apresenta diversas aplicações na agricultura, destacando-se a definição de áreas de manejos específicos e estimativa da produtividade das culturas. Objetivou-se comparar a acurácia de dois índices de vegetação (NDVI e IRVI) na estimativa da produtividade de grãos e de biomassa do feijoeiro cultivado sob doses de nitrogênio em quatro estádios fenológicos. O experimento foi realizado na safra de inverno de 2018. O experimento apresentou 5 tratamentos, sob doses de N em cobertura (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
1
Order By: Relevance
“…It was observed that productivity in the current study was 101 and 82% higher than the average Brazilian productivity in the first and second common bean harvest (Figure 11). Using this general average of treatments with CSS application, it was also noted that the present productivity surpassed the other studies as well, such as that by Sandrini et al [45], whose common bean productivity was 2329 kg ha −1 as a function of nitrogen application rates. In addition, Prates et al [23] reported a linear increase in soybean productivity with the application of CSS rates in the first year of soybean cultivation.…”
Section: Attributessupporting
confidence: 48%
“…It was observed that productivity in the current study was 101 and 82% higher than the average Brazilian productivity in the first and second common bean harvest (Figure 11). Using this general average of treatments with CSS application, it was also noted that the present productivity surpassed the other studies as well, such as that by Sandrini et al [45], whose common bean productivity was 2329 kg ha −1 as a function of nitrogen application rates. In addition, Prates et al [23] reported a linear increase in soybean productivity with the application of CSS rates in the first year of soybean cultivation.…”
Section: Attributessupporting
confidence: 48%
“…Em vista da necessidade de obter mais informações sobre os sistemas agrícolas, os avanços em tecnologias levaram ao uso de sensores remotos que permitem estimar potencialmente componentes da produção agrícola (ZERBATO et al, 2016). A partir da radiação refletida, coletada por estes sensores, é possível adquirir informações relacionadas ao tipo de cultura, condições fenológicas ou nutricionais da cultura e produtividade, bem como identificar a ocorrência de doenças e pragas (SHARIFI, 2020;FERREIRA et al, 2016;XIA et al, 2016;SANDRINI et al, 2019;PARK et al, 2016;ELAZAB et al, 2016;ARANTES et al, 2021;ABDULRIDHA et al, 2019;YE et al, 2020;YUAN et al, 2017;ORLANDO, 2020;DIAO, 2020;MARTINS et al, 2020).…”
Section: Introductionunclassified